Trends in Microlearning and Literacy Integration in Digital Learning - Dinihari, Yulian; Santosa, Imam; Ayuardini, Marisha; Yulistiana (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The rapid advancement of digital technology has spurred the adoption of microlearning as a flexible and learner-centered instructional strategy. This study explores the convergence of microlearning and literacy development particularly digital, media, and critical literacy through a qualitative systematic literature review of 30 peer-reviewed articles published between 2018 and 2024. The findings reveal that microlearning enhances learning outcomes, supports cognitive engagement, and fosters essential 21st-century competencies. Key features such as multimodality, gamification, and mobile accessibility contribute to increased motivation and personalized learning experiences. Additionally, microlearning empowers both students and educators by promoting self-directed learning and digital competence. Despite implementation challenges like content fragmentation, the strategic design of modular and cohesive materials can mitigate these limitations. Overall, microlearning is not merely a trend but a transformative tool in building inclusive, adaptive, and sustainable digital learning ecosystems. This study offers a conceptual framework for integrating microlearning into future curriculum design and instructional practices.